2019
DOI: 10.3390/su11154183
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Influencing Factors on CO2 Emissions in the Yangtze River Delta during Urbanization

Abstract: The Yangtze River Delta (YRD) is China’s largest urban agglomeration with a rapid urbanization process. This paper analyzes the dynamic relationship between urbanization rate, energy intensity, GDP per capita, and population with CO2 emissions in YRD over 1990–2011 based on the extended STIRPAT model, impulse response function, and variance decomposition. A support vector machine model was constructed to further predict the scenarios of YRD’s CO2 emissions from 2015–2020. The results show that YRD’s CO2 emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
(79 reference statements)
1
7
0
Order By: Relevance
“…Yuan, Rodrigues, Wang, Tukker, and Behrens [31] found that urbanisation increased household GHG footprints in emerging regions in China. The significant and positive impact of urbanisation on environmental degradation is also confirmed by other studies [30,32,33]. Economic growth driven by urbanisation also increases carbon dioxide emissions, i.e., contributes to environmental degradation [9].…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Yuan, Rodrigues, Wang, Tukker, and Behrens [31] found that urbanisation increased household GHG footprints in emerging regions in China. The significant and positive impact of urbanisation on environmental degradation is also confirmed by other studies [30,32,33]. Economic growth driven by urbanisation also increases carbon dioxide emissions, i.e., contributes to environmental degradation [9].…”
Section: Introductionsupporting
confidence: 63%
“…According to other authors' findings, higher rates of urbanisation, energy carbon emission coefficients, and energy intensities will result in larger carbon emissions [32]. However, greater than population growth and urbanisation rates, GDP per capita contributes more to CO 2 emissions, and this contribution rate is rising [33]. Other authors also emphasise that the socioeconomic elements of economic expansion, urbanisation, and industrialisation will result in more CO 2 emissions, while advancements in service and technology levels may result in lower CO 2 emissions [30].…”
Section: Comparison With Previous Studiesmentioning
confidence: 97%
“…According to the ndings of the study carbon emissions intensity, energy intensity, gross domestic products, and population are the main causing agents of CO 2 emissions. Xue et al [9] studied the connection between energy intensity, GDP, population and urbanization with the CO 2 emissions in the Yangtze River Delta, China. The time for this study was 1990 to 2011.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zu et al [8] Optimal Precision Alimi et al [9] Linear, Poly, RBF Precision, Recall, F-Score Xue et al [10] RBF Accuracy Olivares-Mercado et al [12] RBF Precision, Recall, Accuracy, F-Score Joshi et al [59] RBF Accuracy Ahmad et al [16] RBF Accuracy Aruna et al [60] RBF Accuracy Abdelaal et al [15] RBF AUC You and Rumbe [20] Poly, RBF, Sigmoid Accuracy Huang et al [17] RBF Accuracy…”
Section: Studies Kernels Evaluationmentioning
confidence: 99%
“…The SVM methodology, which belongs to intellectual machine-learning algorithms, has been actively used within the field of sustainability research [8][9][10][11][12]. Among the machine-learning algorithms, such as linear discriminate analysis, decision trees, logistic regression, naïve Bayes, artificial neural networks and k-nearest neighbor, SVM is a tried and tested algorithm that has gained much trust amongst academics [13,14].…”
Section: Introductionmentioning
confidence: 99%